An Innovative Method for Estimating the Spatial Distribution of Parking Demand in Different Areas - Nafiseh Hosseini; Ali Khoshgard (Civil Engineering Journal, 2018)
Parking facilities in the urban road network are of the most essential parts of the transportation and traffic system. Considering that many users are not interested in parking in or near the destination zone, or in some cases it is not basically possible to park in this area, the parking demand in each area is not merely associated with the actual land use of that area and is sometimes affected by the land use of the surrounding area. Therefore, estimating the spatial distribution of parking demand is essential to accurately determine the real parking demand, especially in non-marginal urban areas. In conventional methods of estimating the parking demand in each area, it is assumed that the parking areas are located in the same area or distributed uniformly in the surrounding areas, without considering the desirability of the surrounding areas, which has sometimes led to unrealistic estimations. Accordingly, new methods, capable of estimating the real parking demand in each area, are needed. In present study, an innovative method is proposed to predict the spatial distribution of parking demand and then it is applied to the central area of Tehran.